2016
DOI: 10.1080/13557858.2016.1244736
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health disparities among disadvantaged older adults in ethnically diverse urban neighborhoods in a Middle Eastern country

Abstract: The social context in which older adults live and their financial security are key in explaining disparities in SRH in marginalized communities. Social capital and economic security, often overlooked in policy and public health interventions, need to be integrated in dimensions of well-being of older adults, especially in post-conflict settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…SRH is also used for cross-country comparisons [23,24,25,26,27,28,29] and policy development [30,31,32,33]. It is used as a reflection of health disparities and inequality [34,35,36,37]. SRH is also used to track the subjective health of individuals with index psychiatric or medical conditions [38].…”
Section: Introductionmentioning
confidence: 99%
“…SRH is also used for cross-country comparisons [23,24,25,26,27,28,29] and policy development [30,31,32,33]. It is used as a reflection of health disparities and inequality [34,35,36,37]. SRH is also used to track the subjective health of individuals with index psychiatric or medical conditions [38].…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging the transformed role of women in bearing the economic burden of a family, the report equally highlighted women's increased marginalisation, where 'political oppression, extremism, widespread violence, and exploitation' compromised women's possibility of social participation (Syrian Center for Policy Research 2017, p. 6). We add our recommendations to existing ones to promote the use of social capital building approaches, such as community-driven development, job creation, and education as peace building blocks in post-conflict settings (Idres 2016;Sibai et al 2017). This is a topic that will require considerable further research, as post-conflict rebuilding becomes possible in urban Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility of patients from minority ethnic groups to healthcare services has been recognized as a challenge in many societies world-wide, and such inequality has been especially identified among the elderly population [24]. Walton & Anthony (2017) [5] found that while Latino, Black and Native American elderly individuals utilized less medical services than white peers, they expressed higher needs for utilization rates of medical services, even when other factors such as health needs, socio-economic levels or the medical systems’ features are accounted for.…”
Section: Ethnic Inequality Within the Elderly Population In Utilizingmentioning
confidence: 99%